Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 4 - Calculating the Derivative - 4.3 The Chain Rule - 4.3 Exercises - Page 225: 8


$f(g(x))=-\dfrac{8}{5}x-23$ $g(f(x))= -\dfrac{8}{5}x+\dfrac{29}{5}$

Work Step by Step

Substitute g(x) in f(x): $f(g(x))= -8(\dfrac{x}{5}+4)+9=-\dfrac{8}{5}x-23$ Substitute f(x) in g(x): $g(f(x))= \dfrac{-8x+9}{5}+4 = -\dfrac{8}{5}x+\dfrac{29}{5}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.